Statistical modeling, optimization and characterization of andrographolide loaded emulgel for its therapeutic application on skin cancer through enhancing its skin permeability - N. V. L. Sirisha Mulukuri; Sujeet Kumar; Moumita Dhara; Gupta Dheeraj Rajesh; Pankaj Kumar (Elsevier, 2024)
Andrographolide is a natural diterpene lactone with multiple biological effects. In the present study, a total of 11 andrographolide-loaded emulgels (ANG 1- ANG 11) were prepared by emulsification and solvent evaporation method using flaxseed oil and xanthan gum in different ratios, as suggested by the Design-Expert software. A 2-factor-5-level design was employed with different responses including spreadability, extrudability, viscosity, and drug release after 1 h (h) and 24 h. Based on the Design-Expert software response, the optimized emulgel ANG 12 was formulated and evaluated. The 24 h In-vitro drug release was found to be 95.7 % following Higuchi kinetics. Ex-vivo skin retention of 784.78 ug/cm2 was observed during the study. MTT assay performed on Human epidermoid carcinoma (A-431) cells demonstrated cell growth arrest at G0/G1 and G2/M phase after 24 h of ANG 12 treatment (IC50: 11.5 µg/ml). The cellular permeability of ANG-12 was assessed by Fluorescein isothiocyanate (FITC) assay. Compared to untreated cells (0.54 % uptake) the ANG-12 treated cells had shown 87.17 % FITC permeation. The biocompatibility study performed on non-cancerous human dermal fibroblast cells (HDF cells) shows 91.54 % viability after 24 h of the treatment showing the non-toxic nature of ANG-12. Confocal imaging had shown a significant time-dependent increase in in-vivo cellular uptake with enhanced, progressive penetration of the emulgel into the skin. An in-vivo skin irritation study conducted on Swiss albino mice confirmed the safety aspects of the ANG 12. Hence, it can be concluded that nanoemulgel of andrographolide (ANG 12) could be a novel approach to treating skin cancer.